Temas geradores e gestus: a construção de um procedimento teatral do ponto de vista do encenador - Bittencourt, Amanda Stahl Homem de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The objective of the present work is to elaborate a procedure for the beginning of a theatrical production, focused on the work of the director. The intention is to provide a proposal that assists in the collection of scenic material, the creation of an aesthetic concept and the deepening of the thematic studies related to the piece. For this, an intersection between the generating themes, of Paulo Freire and the gestus, of Bertolt Brecht is sought. It is considered that these two authors have perspectives criticism and social questioning within their works, which is directly related to the perspective of this research and the theatricality investigated by the author. This proposal will be structured theoretically, applying these two theories in the construction of this procedure that is intended for use in the rehearsal room or in a formal and non-formal education system.

O objetivo do presente trabalho é elaborar um procedimento para o início de uma montagem teatral, focada no trabalho do encenador. O intuito é fornecer uma proposta que auxilie no levantamento de material cênico, na criação de uma concepção estética e no aprofundamento dos estudos temáticos relacionados à peça. Para tanto, busca-se uma intersecção entre os temas geradores, de Paulo Freire e o gestus, de Bertolt Brecht. Considera-se que estes dois autores têm perspectivas de crítica e questionamento social dentro de suas obras, o que se relaciona diretamente com a perspectiva desta pesquisa e da teatralidade investigada pela autora. Esta proposta será estruturada no plano teórico, aplicando estas duas teorias na construção deste procedimento que se destina à sua utilização na sala de ensaio de grupos teatrais ou em um sistema (formal e não formal) de educação.
Keywords: Brecht, Bertolt, 1898-1956; Freire, Paulo, 1921-1997; Representação teatral - Estudo e ensino; Teatro (Literatura) - Técnica; Acting Study and teaching